2019
DOI: 10.1002/mdp2.118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strut cross section and strut defect on tensile properties of cubic cellular structure

Abstract: Selective laser melting (SLM) process is used to produce complex geometries for various applications such as biomedical and aerospace industries. However, one of the limitations with respect to this process is the introduction of geometrical defects during the manufacturing process. The presence of these defects makes it difficult to predict their mechanical behaviour. The present work focuses on the cubic lattice structures and their geometrical deviations from the as-designed structures caused by defects lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The struts in the FE model were elliptical in cross-section with an increased thickness as discussed in the article under publishing. 52 The porosity of the FE model was similar to the measured porosity values. A 5 × 5 × 5 FE model was used in order to simulate the tensile and compression test in the elastic region.…”
Section: Methodssupporting
confidence: 72%
“…The struts in the FE model were elliptical in cross-section with an increased thickness as discussed in the article under publishing. 52 The porosity of the FE model was similar to the measured porosity values. A 5 × 5 × 5 FE model was used in order to simulate the tensile and compression test in the elastic region.…”
Section: Methodssupporting
confidence: 72%
“…Muller et al [107] found that a certain level of randomization improves the mechanical properties while Raghavendra et al [108] reported regular structures having higher values of strength. Other works tested lattice structures to compare their properties with the natural bone [7,87] or to validate the related FEM simulation [120,121].…”
Section: Tensile Testmentioning
confidence: 99%